Analysis Thin Film Polymer Composite of Polymethyl Metacrylate-Reactive Mesogen Diacrylate and its Conductivity Properties - Afrizal, Afrizal; Budi, Setia; Ambarwati, Annisa; Riswoko, Asep (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
This study aimed to investigate the impact of temperature during the UV curing process on the formation of a thin film polymer composite composed of polymethyl methacrylate-reactive mesogen diacrylate. The thin film polymer composite was successfully synthesized using the UV curing method, and the reactive mesogen diacrylate employed in this study was RM 82. Methyl methacrylate and RM 82 were polymerized through UV curing with photopolymerization additions using Benzoyl Peroxide as the initiator. The photopolymerization process was performed at various temperatures of 125℃, 150℃, and 200℃ for 5 minutes. The thin film photopolymerized at 125℃ and 150℃ exhibited greater transparency than the thin film photopolymerized at 200℃. The FTIR results indicated the breakdown of the vinyl group and the triple bond. The FTIR spectrum displayed successful polymerization, with peak wave numbers of 1147 cm-1 and 1221 cm-1 for PMMA in the presence of C-O-C in the ester and a peak at 1465 cm-1. The SEM results demonstrated that the thin film photopolymerized at 200℃ had become distorted. The XRD results revealed that the thin films of all variations were semi-crystalline. Meanwhile, the conductivity test revealed that the thin film photopolymerized at 125℃ had a conductivity value of 2.095 x 10-12 S, while the photopolymerized thin film at 150℃ had a conductivity of 2.14 x 10-12 S. Hence, the addition of reactive mesogen RM82 by 50% may increase the conductivity value of the thin film, making it a potential material for applications as a thin film polymer composite of PMMA-RM 82.